Improvement Skills of Tanjung Balik Youth Generation with Training on Youtube Video Production of Local Wisdom and Natural Wealth of Tanjung Balik West Sumatera - Siska Alicia Farma; Ganda Hijrah Selaras; Yoszi Mingsi Anaperta; Ilham Sepriadi; Frisca Rinaldi Putri (Fakultas MIPA Universitas Negeri Padang, 2023)
Biodiversity is Indonesia's natural wealth. Nagari Tanjung Balik, IX Koto Atas District, Solok Regency is a Nagari that has unique natural wealth. Ngalau is part of the wealth of Biodiversity that must be preserved. However, this area has received less attention because it has not been properly promoted. This is because the ability of residents to introduce their area through various platforms is still lacking. For this reason, it is necessary to have YouTube-based community multimedia production training. The form of activity that will be carried out is active participation through promotional strategy seminars, multimedia production training, and promotional videos as well as the use of YouTube as a village promotion media. The results of these activities resulted in 3 best video winners. The satisfaction survey showed that 58% of participants were very satisfied and 42% satisfied. Improvements in knowledge, attitudes and skills were also seen after the activity.